(untitled) (Journal of the College of Basic Education, 2022)
This research deals with the rebellious poetic impact left to us by the poets of the twentieth revolution, and the role they played in moving the national and religious feeling, in combating the English occupation. and how their poems dealt with the revolution, and the second topic is post-revolution poetry, which is no less important than poetry at the time of the revolution; And the suggestive poetic images associated with the poetry of the revolution, and the impact they left on Iraqi society.